Indexes to the collected works of John Stuart Mill - O'Grady, Jean, 1943-; Robson, John M., 1927- (Mill, John Stuart, 1806-1873. Works. 1963, 1991)
The primary aim of the edition is to present fully collated texts of those works which exist in a number of versions, both printed and manuscript, and to provide accurate texts of those works previously unpublished or which have become relatively inaccessible. The series is complete.